Proceedings of the 8th International Conference on Pervasive Computing Technologies for Healthcare 2014
DOI: 10.4108/icst.pervasivehealth.2014.254958
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Cues for ADHD Parenting Strategies Using Mobile Technology

Abstract: Parenting is always demanding, but families coping with neurodevelopmental disorders, such as ADHD, experience unique challenges. To address these challenges, research in the area of Parental Behavioral Therapy is accelerating. This type of therapy focuses on behavioral strategies that, if practiced regularly, can have a positive impact on the child's long-term behavior, as well as a reduction in parental stress. While these strategies are simple, there are hurdles to putting them into practice. First, parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…Furthermore, a different example of an assistive technology is the ParentGuardian system that provides in situ Parental Behavioral Therapy (PBT) cues for parents of children with ADHD, in order to support parents to better manage stressful situations [24]. The ParentGuardian system uses changes in skin conductance, measured by an Electro-Dermal Activity wristband, to estimate the stress level of the parent.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a different example of an assistive technology is the ParentGuardian system that provides in situ Parental Behavioral Therapy (PBT) cues for parents of children with ADHD, in order to support parents to better manage stressful situations [24]. The ParentGuardian system uses changes in skin conductance, measured by an Electro-Dermal Activity wristband, to estimate the stress level of the parent.…”
Section: Related Workmentioning
confidence: 99%
“…The ParentGuardian system uses changes in skin conductance, measured by an Electro-Dermal Activity wristband, to estimate the stress level of the parent. When a high level of stress is detected, the parent is prompted with a combined textual and visual reflective strategy on their smartphone and on a peripheral display to remind them to use PBT strategies [24]. From their studies, Pina et al found that in situ cues for parents could assist the parents to remember to use the PBT strategies during moments of need [24].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, learning self-control is one of the key aspects of SEL; it relies strongly on identifying a problematic situation and then to calm down before it is "too late" and emotions are already running high. One opportunity for technology in this setting can draw on the maturing HCI research on in-the-wild stress detection drawing on physiological data or speech prosody, for example, Hernandez et al [2011], Poh et al [2010], Pina et al [2014], Zeng et al [2009], and Ertin et al [2011]. We envision that such data could be used to support the learners in becoming aware of their heightened arousal (e.g., through a private tactile reminder such as FitBit wrist vibration), which can serve as a cue to start the self-calming/self-control mechanisms taught in class.…”
Section: Embedding Of Learnt Skills Into Other Settingsmentioning
confidence: 99%
“…Moreover, SEL designers have deep understanding of how best to work with such cues and triggers once these are identified. An example of initial work in this direction is Pina et al [2014], who designed a system for parents of Attention Deficit Hyperactivity Disorder (ADHD) children, delivering in-the-moment cues and strategies to manage stress during everyday activities. Overall, the initial studies point to the potential of such technologies, but also point to many practical issues to be addressed, including whether such systems are robust and precise enough for immediate inclusion into the SEL curricula, and how could these be best embedded in the existing programs to most appropriately exploit this potential.…”
Section: Embedding Of Learnt Skills Into Other Settingsmentioning
confidence: 99%